RESPON EMPAT VARIETAS KEDELAI (Glycine max (L).Merril )TERHADAP PEMBERIAN BEBERAPA DOSIS PUPUK FOSFOR - Riawati '; Aslim Rasyad; Wardati ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The objective of this study is determine response of four varieties on various rates of phosphorous fertilizer. The field experiment was arranged in a with  randomized complete block design three replications. Seed of each cultivar was planted in a plot of 3 m by 2 m with planting space of 40 cm between rows and  20 cm within a row. Parametersobserved wereplant height, time to flowering, time to harvest, number of podsperplant, number of filled pod per plant, numberof seeds per plant, seed weightperplant, yield perm2, and 100-seed weight.Application of 25 kgP2O5per ha increased plant height, number of filled pods, the number of seeds per plant and seed weight per plant and shorthened time to floweringand harvesting age. Grain yield per m2 ofWilisand Gema was higher if fertilized by 50 P2O5per hathan control and 25 P2O5 per ha.  On the other ways, grain yield per m2 ofBurangrangand Kaba varietieswas not affected significantly by application of P fertilizer.   Keywords :Soybeanvarieties, phosphorus Fertflizer, yield components, grain yield